The Virtues Basics According to Ibnu Hazm al-Andalusi | أصول الفضائل لدي ابن حزم الأندلسي - Willy Oktaviano (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
Arguably, the main honor attitude in Islam is treating people equally or being fairness and justice. Fairness can be defined as placing something based on its proper situations and conditions. Ibnu Hazm al-Andulisi who is an influential imam in the Islamic world, elaborates that the basic principle of honor attitudes is fairness, which is not only treating and understanding people properly, but also being useful for many people. Importantly, this fairness should be committed honorably and sincerely.